2019
DOI: 10.3386/w25787
|View full text |Cite
|
Sign up to set email alerts
|

Can Economic Policies Reduce Deaths of Despair?

Abstract: for helpful suggestions, and to Christopher Ruhm for his assistance with recoding the CDC causes of death data. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…For example, higher minimum wages and the earned income tax credit have been shown to reduce suicides but not drug poisoning deaths among adults with lower educational attainment. 31 , 32 Another study by Ruhm 33 found that economic factors are likely to explain only a small fraction of drug poisoning deaths, concluding that the availability and use of drugs is more likely to be the key driver. Ruhm 33 found no association of economic factors with suicide and alcohol-induced death rates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, higher minimum wages and the earned income tax credit have been shown to reduce suicides but not drug poisoning deaths among adults with lower educational attainment. 31 , 32 Another study by Ruhm 33 found that economic factors are likely to explain only a small fraction of drug poisoning deaths, concluding that the availability and use of drugs is more likely to be the key driver. Ruhm 33 found no association of economic factors with suicide and alcohol-induced death rates.…”
Section: Discussionmentioning
confidence: 99%
“…Causal models suggest that increasing both by 10% would have prevented 1230 suicides annually, but have no impact on drug overdoses. 30 Another study found that higher state-wide union density was associated with lower mortality rates for suicide and overdose. 31 In a study directly relevant to this one, a difference-in-differences approach estimated an association between county-level automobile assembly closures, from 1999 to 2016, and opioid mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on the efficacy of strategies to reduce suicide among adolescents, including antidepressants for those with depression, is mixed 3637. Recent evidence suggests that policies raising the incomes of low wage workers are associated with a reduction in suicides, with a 10% increase in the earned income tax credit associated with a 5.5% decline in suicides and a 10% increase in the minimum wage associated with a 3.6% decline in suicides 38…”
Section: Discussionmentioning
confidence: 99%